(untitled) - Nations, Scott (Hoboken, New Jersey, 2014)
This book tells us about: Generate monthly income by selling covered strangles Use call spreads to recover from a losing stock position Protect an existing stock position using put diagonals Discover the best strategies for directional market plays
Keywords: Options (Finance),Tùy chọn (Tài chính),Phân tích đầu tư; Mathematics,Toán học; Investment analysis